Violation of Bloch's Law That Specifies Reciprocity of Intensity and Duration with Brief Light Flashes. (December 2013) - Greene, Ernest
For more than a century researchers have been reporting that the visual impact of a very brief flash is determined by the quantity of photons that the flash delivers. This has been variously described as the Bunsen-Roscoe Law or Bloch's Law, often specified as reciprocity of intensity × duration. Prior research found no evidence for such reciprocity when microsecond-duration flashes from a light-emitting diode array were used to display the major contours of nameable shapes. The present work tested with flash durations ranging up to 100 ms and also found no reciprocity. This departure from classic principles might be due to the specific range of wavelengths of the light-emitting diodes and to a mesopic level of ambient light, which together would preclude activation of rods. The reciprocity of intensity and duration may only be valid with full dark adaptation and very dim flashes that activate rods.